Mapping the distribution of small bowel angioectasias. (4th May 2019) - Davie, Matt; Yung, Diana E.; Douglas, Sarah; Plevris, John N.; Koulaouzidis, Anastasios
Abstract: Background: Angioectasias are a prominent cause of small bowel (SB) bleeding frequently identified during capsule endoscopy (CE). Subsequent management depends upon grade/severity and location. There is increasing evidence that the location of SB angioectasias is not random. We aimed to map the distribution of SB angioectasias, and assess whether this impacted clinical outcomes. Materials and methods: Retrospective study examining CEs performed over a 10-year period at a tertiary referral centre. Information regarding number, location, and Saurin classification (P0–2) of SB angioectasias was collected. Clinically significant angioectasias (P1/P2) and active SB bleeding were analysed further. Outcomes of patients with P2 angioectasias or active SB bleeding were recorded. Results: 164 SBCE examinations reported angioectasias. 554 P1-2 angioectasias and active bleeds were seen, 435 (78.52%) within the first tertile of SB transit time (SBTT). 277 (50%) angioectasias were identified within the first 10% of SBTT. 40/75 (53.3%) patients with >1 P2 angioectasia and/or active bleed were referred for intervention. Of initial interventions, 24 patients underwent upper GI endoscopy; 13 underwent double balloon enteroscopy (DBE). 9/37(24.3%) had no identifiable angioectasias on endoscopy. Of those receiving ablative therapy, 20/28 (71.4%) re-presented with iron-deficiency anaemia or bleeding. In this group, average angioectasia position was 15.6% of SBTT, compared with 7.9% in those who did not re-represent ( p  = 0.344). Patients who re-presented had an average 1.6 additional P1 angioectasias, compared with 7.6 amongst those who did not return ( p  = 0.017). Conclusions: Clinically significant angioectasias are overwhelmingly located within the proximal SB. The majority are within reach of conventional endoscopy. However, AEs are often multiple and many patients re-present following intervention.